Wound-Healing Following Negative-Pressure Wound Therapy with Use of a Locally Developed AquaVac System as Compared with the Vacuum-Assisted Closure (VAC) System. (20th November 2019) - Cocjin, Hansel Gould B.; Jingco, Jair Kimri P.; Tumaneng, Franklin Delano C.; Coruña, Jose Maria R.
Abstract : Background: Negative-pressure wound therapy (NPWT) gained widespread clinical use after its introduction in the 1990s because of its many beneficial effects on the wound environment. However, high treatment costs have limited its use in third-world countries. The present study compares a low-cost, locally developed NPWT system with a commercially available system in terms of efficacy, reliability, ease of application, and safety. Methods: This prospective, randomized controlled trial involved 36 patients who were managed with NPWT with either a low-cost, locally developed system (AquaVac) or a commercially available Vacuum-Assisted Closure Advanced Therapy System (VAC ATS; KCI). The low-cost NPWT system described consists of a converted aquarium pump as a reusable vacuum source and a dressing system that can be found in the hospital supply room: food plastic wrap as an occlusive drape, surgical gauze as wound filler, nasogastric tubes as tubing, and used intravenous (IV) bottles as effluent canisters. The purpose of the study was to compare the 2 systems in terms of (1) time to apply the dressing, (2) exudate levels, (3) amount of granulation tissue, (4) wound size reduction, (5) average cost of treatment, (6) visual analog scale (VAS) pain scores, and (7) complications. Results: The experimental low-cost system had a small but statistically insignificant advantage over the commercially available system in terms of application time, pain during dressing changes, and wound contraction percentage. The 2 systems were comparable in terms of the amount of exudate, granulation tissue coverage, and VAS scores during the course of treatment. No wound or periwound complications were observed. The systems were significantly different in terms of cost, with the AquaVac system being 7 times less expensive than the VAC ATS system ($63.75 compared with $491.38 USD). Conclusions: The low-cost AquaVac system was shown to be comparable with the commercial VAC ATS system, suggesting that it is an effective and safe alternative method for NPWT in resource-challenged settings. Level of Evidence: Therapeutic Level I . See Instructions for Authors for a complete description of levels of evidence.